Mathematical modeling of magnetization information for flowing spin-1/2 nuclei subjected to standard MRI RF excitation pulse sequences - Amurao, Maxwell Leland R. (Animo Repository, 2002)
This study develops and has attained a mathematical framework for modeling Transverse and Longitudinal Magnetization of several distinct spin-1/2 subpopulations that are located within a prescribed volume deriving expressions for the Transverse and Longitudinal Magnetization for all spin subpopulations that remain within a prescribed volume as they are subjected to the Spin Echo, Gradient Echo, and the CPMG RF excitation pulse sequences and subjecting the developed mathematical framework to plug, laminar, periodic-plug and periodic-laminar flow conditions to calculate the net Transverse and Longitudinal Magnetization of a prescribed volume.